La responsabilidad penal de las personas jurídicas, frente al delito de cohecho. - Jaya García, Cristina Elizabeth (2023)
The Comprehensive Criminal Organic Code, from a new legal perspective, has determined that companies, entities and legal corporations will have criminal liability for the unlawful actions that they generate and from which they benefit, establishing sanctions such as closure, fine, dissolution among others, which will be applied whenever it is demonstrated that there was a direct benefit for the legal entity from that illegal act, but in the event that the representatives of legal entities are the only beneficial ones, the criminal legislation will sanction them independently for the act or omission committed. The present investigation has as main objective to analyze legally and doctrinally the criminal responsibility of legal persons against the crime of bribery. The study is developed under a mixed approach, which gathers direct information on what the criminal liability of legal persons and the crime of bribery implies, from the perception of professionals specialized in the criminal branch to whom the techniques of survey and interview. The results of the investigation reveal that the legal representatives of legal persons hide behind these entities to commit the crime of bribery and seriously harm the public interest of the State, concluding that the sanctions determined in the criminal type of bribery should be extended, since They are not proportional to the damage that is done and the dishonor generated by the good name of public institutions. Keywords: Bribery, Legal Entity, Criminal Liability, Public Interest, public official.